Outcomes of Conventional Amplification for Pediatric Unilateral Hearing Loss - Briggs, Lauren (2011)
OBJECTIVES: Although children with unilateral hearing loss (UHL) are at-risk for educational difficulties and behavioral problems, research in treatment outcomes is limited. Previous studies suggested that children with UHL would benefit from frequency-modulated (FM) assistive devices only. The objective of this study was to examine whether children with UHL would benefit from using a conventional hearing aid in the poorer-hearing ear. METHODS: Eight children, ages 7 to 12 years, with mild to moderately severe UHL, their parents and teachers participated in this study. Participants were fit with digital hearing aids using pediatric prescriptive targets. Primary outcome measures were speech perception tests in quiet and noise and subjective assessments from participants, parents and teachers, administered prior to and after three months of hearing aid use. RESULTS: Group average speech perception scores showed no significant aided benefit or detriment in any of the conditions tested. However, subjective assessments showed large significant aided benefits at home and school according to the children and their parents, and in quality of life as reported by the children with UHL. CONCLUSION: Overall, the results suggest a hearing aid trial should be considered for children with mild to moderately severe UHL with individual monitoring for benefit.